Peningkatan Kompetensi Guru SMP Mata Pelajaran Bahasa Inggris di Jakarta Barat - Syamsudin, Oom Rohmah; Hasbullah; Suryana, Andri; Suendarti, Mamik (Darma Cendekia, 2022)
The purpose of this activity is to provide additional insight to teachers to meet the competency standards as professional teachers set by the government. Indonesian teachers can signify professional teachers if they require all 10 teacher competencies. The two qualifications they need to acquire are education and training and being able to plan and conduct the learning process according to their expertise. Abdimas team of Post Graduate Program Indraprasta University works hand in hand with the Center for Competency Development for Education and Vocational Educators of West Jakarta (P2KPTK2 Jakarta Barat) supporting the teachers to realize their goals of being professional teachers by accommodating an activity of short training in the pedagogic matter, especially in the difference of students characters as a basis for designing a lesson along with enrichment of English learning materials for junior high school level. The method used in this event is observation as well as the discussion with the teachers and P2KPTK2 concerning their needs in the topics mentioned. As a result of this online activity, teachers were very enthusiastic: this can be seen from the post-test score which was better than the pre-test score. Participants also hope that similar activities can be conducted on an ongoing basis as an update of their pedagogic and English skills.